2008
DOI: 10.1111/j.1937-8327.1996.tb00740.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Practices of Instructional Designers and Organizational Supports and Barriers

Abstract: The overall goal of this study was to determine the status quo of evaluation efforts of instructional designers as part of a systematic instructional system. This descriptive research investigated what organizational and managerial frameworks are required to sustain the evaluate component of systematic instructional design. Specifically, this survey: 1) Identifies and describes current evaluation practices and strategies of instructional designers within corporate and higher educational settings, 2) Describes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 1 publication
1
9
0
2
Order By: Relevance
“…Based on the findings of this study, which correspond to the findings from Moller and Mallin (), Twitchell et al . (), Pulichino () and ASTD (), two of the primary reasons for this appear to be related to organizational support of evaluation activities.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Based on the findings of this study, which correspond to the findings from Moller and Mallin (), Twitchell et al . (), Pulichino () and ASTD (), two of the primary reasons for this appear to be related to organizational support of evaluation activities.…”
Section: Discussionsupporting
confidence: 92%
“…Surprisingly, there have been only a small number of studies that investigated barriers to conducting behavior‐based Level 3 and results‐based Level 4 evaluations in organizations. Moller and Mallin () gathered qualitative data from their survey of instructional designers, asking them to discuss the presence of organizational barriers that hindered their efforts to conduct evaluations at any level. Eighty‐eight per cent of the respondents stated that such barriers existed in their organizations, with the dominant barrier being related to a lack of time and other resources to conduct evaluations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…achievement. Yet merely 20% of those surveyed correctly identified methods for results evaluation (Moller & Mallin, 1996;Wang and Wilcox, 2006). Brown & Gerhardt (2002) concluded that companies expend even less effort in evaluating the instructional design process (Nadler & Nadler, 2012;Wang & Wilcox, 2006).…”
Section: Literature Review and Identification Of The Challenge To Be mentioning
confidence: 99%